deriving sentences using inference ruels and logical dequivalences. Propositional Lgc

ii.) derive the statements using inference rules and logical equivalences for propositional logic.

i.(R->S)^Q

ii. (J^Q)->P

iii. Q->Z

iv.P-> -Q (v) (R->S)->(-H->J)

Code:

`derive Z:`

Q->Z

=Z ?

derive: -P

1. (J^Q)->P

2. P-> -Q (v) (R->S)->(-H->J)

3. ?

c.) derive -(j^Q)

1. maybe (J^Q)->P

2. P-> -Q

3.?

d.)derive -J

1.P-> -Q (v) (R->S)->(-H->J)

2.-H->J == -J->H

3.not sure about this one.

e.) derive H

1..P-> -Q (v) (R->S)->(-H->J)

I'm not sure how to prove it with this one.

Can you please help with this.